2006
DOI: 10.1007/s00270-004-6216-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Protection with 5% Dextrose Solution Blanket During Radiofrequency Ablation

Abstract: A serious complication for any thermal radiofrequency ablation is thermal injury to adjacent structures, particularly the bowel, which can result in additional major surgery or death. Several methods using air, gas, fluid, or thermometry to protect adjacent structures from thermal injury have been reported. In the cases presented in this report, 5% dextrose water (D5W) was instilled to prevent injury to the bowel and diaphragm during radiofrequency ablation. Creating an Insulating envelope or moving organs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 11 publications
1
23
1
1
Order By: Relevance
“…Hydrodissection between the RCC and bowel has been reported to prevent thermal injury by blocking the heat conductance during RFA or cryoablation of a RCC [1,3,5,9]. Kam et al [4] reported that CO 2 instillation and balloon interposition are also useful for protecting the organs adjacent to the RCC from thermal injury.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hydrodissection between the RCC and bowel has been reported to prevent thermal injury by blocking the heat conductance during RFA or cryoablation of a RCC [1,3,5,9]. Kam et al [4] reported that CO 2 instillation and balloon interposition are also useful for protecting the organs adjacent to the RCC from thermal injury.…”
Section: Discussionmentioning
confidence: 97%
“…Bowel perforation has been reported to occur after RFA of liver tumors, leading to serious complications such as abscess formation and sepsis [2]. In order to prevent this complication, imaging-guided instillation of sterile water, 5% dextrose and CO 2 and balloon distraction have been used to increase the distance between the RCC and bowel [3][4][5]. However, these procedures may not only delay RFA but also increase the level of radiation exposure when computed tomography (CT) is the guiding modality.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a relatively large amount of liquid (1-3 L) or continuous infusion is often necessary to ensure adequate protection which can result in patient discomfort following the procedure. 6,[17][18][19][20][21][22][23] We evaluated the feasibility of an alternative to conventional liquids: an aqueous poloxamer 407 (P407) hydrodissection material. Poloxamers are polyethylene oxidepolypropylene oxide-polyethylene oxide (PEO-PPO-PEO) triblock copolymers that traditionally serve as nonionic surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CT guidance is mandatory for left-sided lesions. Displacement of surrounding organs with D 5 W or CO 2 has been described and is a technical point that can make adrenal RFA safer and easier to perform [7,8].…”
Section: Technical Pointsmentioning
confidence: 98%